Sodium Acetate Attenuates Fructose-Induced Mitochondrial Dysfunction and Cardiometabolic Disorders in Pregnant Wistar Rats (Nigerian Journal of Physiological Sciences, 2025)
Cardiometabolic disorder is a leading cause of mortality, and mitochondrial dysfunction plays a significant role in its pathophysiology. The mechanisms by which acetate improves fructose-induced cardiometabolic disturbances in pregnancy remain unclear. This study aimed at investigating the role of acetate in modulating the fructose-induced cardiometabolic risks in pregnancy. Thirty-six female Wistar rats (120-150g) were divided into six groups, n=6. A total of 18 rats were made pregnant and 18 non-pregnant. The groups consisted of control (C), fructose (F), and fructose-acetate (FA). The FA group received 10% (w/v) fructose plus sodium acetate (200mg/kg) and distilled water. After three weeks, animals were anesthetized with ketamine (90mg/kg) and xylazine (10mg/kg). Blood and tissue homogenates were analyzed, and data were expressed as mean ± SEM, with significant difference accepted at p < 0.05. Compared to control, fasting blood sugar (FBS), triglyceride-glucose index (TyG), circulatory free fatty acids (FFA), uric acid (UA), malondialdehyde (MDA), and lactate dehydrogenase (LDH) were significantly higher in fructose-treated pregnant rats, and non-pregnant rats. In contrast, high-density lipoprotein-cholesterol (HDL), pyruvate dehydrogenase (PDH), and cardiac aconitase activities were significantly lower in both non-pregnant and pregnant rats, with a more profound effect seen in pregnant rats. Meanwhile, pregnancy significantly exacerbated the fructose-induced alteration in UA, FFA, TG, HDL and MDA. Fructose-induced cardiometabolic alterations were mitigated by acetate irrespective of the gestational status. Acetate restores mitochondrial oxidative capacity in pregnancy, making it a potential therapeutic agent for improving mitochondrial metabolic activities in debilitating gestational cardiac disorders.